2016
DOI: 10.3389/fmicb.2016.01242
|View full text |Cite
|
Sign up to set email alerts
|

Developing Techniques for the Utilization of Planctomycetes As Producers of Bioactive Molecules

Abstract: Planctomycetes are conspicuous, ubiquitous, environmentally important bacteria. They can attach to various surfaces in aquatic habitats and form biofilms. Their unique FtsZ-independent budding cell division mechanism is associated with slow growth and doubling times from 6 h up to 1 month. Despite this putative disadvantage in the struggle to colonize surfaces, Planctomycetes are frequently associated with aquatic phototrophic organisms such as diatoms, cyanobacteria or kelp, whereby Planctomycetes can account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 33 publications
1
61
0
2
Order By: Relevance
“…Two potential scenarios could be envisioned: either the giant genes of strain NH11 T fulfill other, maybe structural functions, or they might be involved in the formation of yet unknown secondary metabolites. While the latter hypothesis fits to the recent observation of novel antibiotic small molecules from Planctomycetes (Jeske et al, 2016), at least some giant genes are predicted to encode proteins with structural function such as the discussed Fuma_00096. While resolving this issue is beyond the scope of this study, we conclude that the genome of strain NH11 T differs in important aspects from its peers.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Two potential scenarios could be envisioned: either the giant genes of strain NH11 T fulfill other, maybe structural functions, or they might be involved in the formation of yet unknown secondary metabolites. While the latter hypothesis fits to the recent observation of novel antibiotic small molecules from Planctomycetes (Jeske et al, 2016), at least some giant genes are predicted to encode proteins with structural function such as the discussed Fuma_00096. While resolving this issue is beyond the scope of this study, we conclude that the genome of strain NH11 T differs in important aspects from its peers.…”
Section: Discussionsupporting
confidence: 70%
“…These organisms are capable of anaerobic ammonium oxidation, a trait extremely useful for wastewater treatment (Kartal et al, 2013). In particular, members of the order Planctomycetales were found to encode numerous secondary metabolite-related genes and gene clusters (Jeske et al, 2013), that were recently found to be active under conditions that chemically mimicked the interaction with eukaryotes (Jeske et al, 2016). Consequently, Planctomycetes were postulated to be “talented producers” of small molecules and they might represent a yet untapped resource of novel bioactive molecules (Jeske et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we were able to identify three carotenoids present in two pigmented planctomycetal strains, thus contributing to improved characterization of bioactive molecules with potential biotechnological relevance in this phylum of aquatic bacteria (Graca et al ., ; Jeske et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Their periplasm is enlarged and forms large invaginations into the cytoplasm. Several planctomycetal strains are regarded as potential talented producers of as yet uncharacterised small bioactive molecules (Graça et al 2016;Jeske et al 2016;Wiegand et al 2018). Many Planctomycetes possess large numbers of giant genes (Kohn et al 2016;Reva et al 2008) and are amongst the bacterial phyla with the highest number of predicted genes of unknown function (Overmann et al 2017;Wiegand et al 2018).…”
Section: Introductionmentioning
confidence: 99%